Recurrent neutropenia and chronic diarrhea following thymectomy: the good, the bad, and the ugly - Mosunmoluwa Oyenuga; Safia Shaikh; Benjamin Harris; Jyotsana Sinha; Alexandre Lacasse (Greater Baltimore Medical Center, 2021)
Good syndrome (GS) is a rare paraneoplastic syndrome seen before or after diagnosis of thymoma, and its treatment, and is characterized by hypogammaglobulinemia. Rarely, pure white cell aplasia (PWCA) can also be seen which can present as recurrent neutropenia. We describe a 64-year-old man with recurrent sinus infections and previous thymectomy for stage 1 type B2 thymoma presenting with chronic diarrhea and recurrent neutropenia necessitating serial hospitalizations despite repeated antimicrobial treatment. Immunoglobulin levels, including IgM, IgA, IgD, and IgE were undetectable. Flow cytometry also showed absent B cells. Patient was initiated on immunoglobulin replacement therapy with consequent significant clinical improvement. Despite thymectomy, patients can develop thymoma-associated paraneoplastic syndromes, including GS.